2014
DOI: 10.1186/1475-2840-13-93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin and exercise training, alone or in association, on cardio-pulmonary performance and quality of life in insulin resistance patients

Abstract: BackgroundMetformin (MET) therapy exerts positive effects improving glucose tolerance and preventing the evolution toward diabetes in insulin resistant patients. It has been shown that adding MET to exercise training does not improve insulin sensitivity. The aim of this study was to determine the effect of MET and exercise training alone or in combination on maximal aerobic capacity and, as a secondary end-point on quality of life indexes in individuals with insulin resistance.Methods75 insulin resistant patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…A recent study showed a significant decrease in VO 2 max in people with metabolic syndrome following 6 weeks of metformin administration ( 58 ). However, previous investigations in people with prediabetes demonstrated no effect of metformin on CRF when administered without a concomitant exercise intervention and no metformin-associated impairment of the response to an exercise training intervention ( 59 , 60 ). Metformin is reported to inhibit complex 1 of the mitochondrial respiratory chain ( 61 , 62 ).…”
Section: Assessment Of Potential Mechanistic Causes Of Exercise Impaimentioning
confidence: 84%
“…A recent study showed a significant decrease in VO 2 max in people with metabolic syndrome following 6 weeks of metformin administration ( 58 ). However, previous investigations in people with prediabetes demonstrated no effect of metformin on CRF when administered without a concomitant exercise intervention and no metformin-associated impairment of the response to an exercise training intervention ( 59 , 60 ). Metformin is reported to inhibit complex 1 of the mitochondrial respiratory chain ( 61 , 62 ).…”
Section: Assessment Of Potential Mechanistic Causes Of Exercise Impaimentioning
confidence: 84%
“…Physical activity has multiple beneficial effects on general health. Data from animal models and clinical studies have suggested that sufficient physical activity can improve cardiovascular function (Park et al, 2012), glucose metabolism (Boersma et al, 2012, Cadeddu et al, 2014), mood disorders (Cunha et al, 2013, Wegner et al, 2014), and lead to healthy weight maintenance and weight loss (Anderson et al, 2001, Swift et al, 2014). While regular physical exercise can sustain a healthy weight or a weight loss regimen, the range of mechanisms by which exercise contributes to the control of body weight remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that the association with physical training could compensate the negative effects of MET on cardiopulmonary performance. Furthermore, we demonstrated that physical exercise, when personalized and supervised, affected cardiopulmonary parameters and quality of life similar to the combination of MET and exercise [ 11 ]. Moreover, there are limited data for the effect of physical training alone or in combination with MET on LV cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of MET appeared to dampen the effect of exercise [ 10 ]. In a previous study, we showed a significant increase in peak oxygen consumption (peak VO2) after 12 weeks of exercise alone or in combination with MET, whereas MET alone resulted in no improvement in peak VO2 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%